Renewable and non-renewable primary energy factors for Lithuanian A++ buildings’ heating - Grinevičiūtė, Monika; Valančius, Kęstutis (International Conference “Environmental Engineering”, 2023)
Lithuanian A++ buildings are highly energy-efficient, but their heating systems still require energy to operate, and the type of energy used can have a significant impact on the environment. By considering both non-renewable and renewable primary energy sources, policymakers, builders, and building owners can make informed decisions about reducing carbon emissions, improving energy efficiency, and promoting sustainable energy use. This article examines the impact of different heating systems on primary energy (PE) consumption in buildings of different functions (single-dwelling residential building, multi-dwelling residential building, office building) with the same energy class (A++), to determine how much primary energy (renewable and non-renewable) is consumed for building operation and investigate changes in CO2 emissions depending on heat source. Primary energy use is a crucial benchmark for achieving energy efficiency goals in the European Union, but the use and calculation of primary energy factors can be contentious as they can affect the results of various analyses. The study demonstrates that the choice of the heat source is a complex task, as it requires considering the share of renewable primary energy in the final primary energy consumption, particularly in “Nearly zero energy buildings” (Lithuanian A++ buildings) where most of the energy consumed should come from renewable sources.
Keywords: primary energy; non-renewable energy; renewable energy; energy class; energy efficiency; CO2 emissions